The policy of criminalization in private criminal laws - الشمري كاظم عبدالله; عبد زينة عبد الجليل (Journal of Legal Sciences, 2021)
The policy of criminalization in private criminal laws focuses primarily on acts that violate social order, which constitute an attack on interests deserving of criminal protection. This policy is distinguished by its own nature, which stems from the nature of criminalization in these laws, In addition to the law issued by the legislative authority, there are certain cases in which the executive authority has the authority to issue regulations and instructions that are the source of criminalization and punishment in these laws, This policy in private criminal law is based on the criminalization criteria in these laws. The criminal legislator takes the criminality of the nature of the interest, which is often of a changing nature, and the nature of the risk of certain crimes to the interests that the legislator has protected to protect them from criminalization.